PERAN MANAJEMEN TALENTA DAN MANAJEMEN PENGETAHUAN DALAM MENINGKATKAN KINERJA PEGAWAI - Rina Masruroh; Indah Fiki Apriani; Pipih Sopiyan (Universitas Kuningan, 2023)
This research was conducted to determine the effect of talent management and knowledge management on employee performance at the Civil Servant of the Youth, Sports and Tourism Office of Kuningan Regency.This type of research uses a survey method with descriptive and quantitative analysis. The object of this research is the Civil Servant of the Youth, Sports and Tourism Office of Kuningan Regency, with a sample of 57 using a saturated sample. The data collection technique used a questionnaire with an interval scale. The analytical technique used is Multiple Linear Regression Analysis and using the IBM SPSS Statistics 23 Program application. The results of the research that have been analyzed show that simultaneously talent management and knowledge management have a positive and significant influence on the performance of Civil Servants, Youth, Sports and Tourism, Kuningan Regency. While partially talent management has a positive and significant effect on the performance of Civil Servants of the Youth, Sports and Tourism Office of Kuningan Regency. But partially knowledge management has a negative and insignificant effect on the performance of Civil Servants of the Youth, Sports and Tourism Office of Kuningan Regency.